Sustained growth in small enterprises: a process management approach - Rose, T. J. (Cranfield University, 2003)
This thesis illustrates that given the necessary resource and a structured Business Growth Framework, Small and Medium Enterprises can lay the foundation for sustained growth. The author investigated the essence of Small and Medium Enterprises, conducted a literature review in SME growth, and asserted the importance of the application of structure to business processes in achieving sustainable business growth. The author introduced the SME business process structure deficit, assessed its implications on business growth, and elaborated that the business process structure deficit can be addressed through the methodical application of six internationally accepted UK initiatives already available in the SME domain. The thesis establishes the characteristics of Business Growth for SMEs, leading to the development of a Business Growth Framework, based upon a defined set of business processes. This framework supports business growth. The framework provides diagnostic assessment of business process performance, process specific improvements embracing better practice through the innovative application of, for example DTI publications, and internal Benchmarking linking, if desired, to the UK Benchmarking Index. The resulting Business Growth Framework, along with the Business Growth Framework Implementation Methodology have evolved during this research and are the key tools for sustained business growth developed by the author and discussed in this thesis. The benefits of close integration of financial and manufacturing systems, like ERP, with Business Processes is discussed. The author demonstrated that Business Growth could successfully occur amongst Small and Medium Enterprises if approached through a structured methodology. Intentionally no new and complex business models have been proposed. The research showed that there is sufficient literature available in this area already.